The Impact of Globalization on SMEs a Case Study of Mould Fabrication Industry in Wilayah and Selangor - Chen, Sen Chang (1997)
This is a case study to assess the competitive priorities and the strategies of survival of mould fabrication industry in Wilayah and Selangor under the impact of globalisation. Globalisation, on the other hand, is a strategy in which organisation treats the entire world or major regions of it as domain for conducting business. As such, the world has become a global village with borderless communities scattering all over the globe. MNCs under the globalisation view the globe as a huge market to capture economies of scale, cost and culture effectiveness in product standardisation. In addition, they rely on technology innovation to enhance their capabilities in competitive environment. With response to globalisation, some others view that globalisation and liberalisation forces are being exploited by MNCs to frustrate the efforts of developing nations. On the whole, Malaysian SMEs in mould fabrication industry are particularly aware of their competition in terms of quality, cost, time and flexibility in production and services offered. Smaller SMEs, somehow, dislike competition because they are not ready and delicate in market competition. Hence, they do not feel the impact of globalisation directly in their operations. By looking into the comparative prices, strategies and feature of mould industry across nations and SWOT analysis, Malaysian SMEs have got certain strategies in the competitive environment provided actions are taken according to the recommendations given. To sustain competitive advantage, SMEs must learn and assimilate new sources of manufacturing technologies and core competencies that will become the basis of the future industry and technology initiatives.